Standarisasi Kerja Operator Menggunakan Tabel Standar Kombinasi Kerja di Sebuah Perusahaan Otomotif Nasional - Agustinus Ivan Sugiarto; I Nyoman Sutapa (Jurnal Titra, 2017)
The problem faced by company is the difference in PPIC Department between actual result and planned result. The second problem is the low efficiency in bush forming and pin cutting area. Related to that problem, company asked to researcher to do a research on current total workers composition whether it's suitable or not. The method used in this research is standard work combination sheet. The current total workers in bush forming and pin cutting area is proper enough, each area with one operator and one supporter to help both area. The first improvement to do is to divide the task and to shift the role between operator and supporter. Workers with high ability work as supporter to fix machines and workers with moderate ability work as operator. The second improvement is to revise work motion for bush forming and pin cutting operator to be more efficient in movement and time.